2021
DOI: 10.1055/a-1344-8138
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Involvement in COVID-19: Conjunctivitis and More

Abstract: Since the beginning of 2020, SARS-CoV-2, the pathogen of COVID-19, has led to a global pandemic that also affects ophthalmology. Ophthalmologists can be confronted at any time with potentially COVID-19 associated ocular symptoms or manifestations in patients and also become infected through close patient contact. Even without systemic infection, the ocular surface can come into direct contact with aerosols or liquids containing SARS-CoV-2 particles. A smear infection through hand-to-eye contact is also possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
(268 reference statements)
0
12
0
5
Order By: Relevance
“…Other ocular manifestations include dry eye syndrome and episcleritis. 41 Follicular conjunctivitis, 9 , 41 – 44 conjunctival hyperemia, 11 chemosis, epiphora, and increased secretions have been reported. 2 , 28 Increased conjunctival secretions, ocular pain, 9 ocular discharge and redness, 9 photophobia, dry eye, tearing, and conjunctival congestion, as well as xerophthalmia and keratitis, are chronic COVID-19 ocular manifestations.…”
Section: Adults’ Ocular Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other ocular manifestations include dry eye syndrome and episcleritis. 41 Follicular conjunctivitis, 9 , 41 – 44 conjunctival hyperemia, 11 chemosis, epiphora, and increased secretions have been reported. 2 , 28 Increased conjunctival secretions, ocular pain, 9 ocular discharge and redness, 9 photophobia, dry eye, tearing, and conjunctival congestion, as well as xerophthalmia and keratitis, are chronic COVID-19 ocular manifestations.…”
Section: Adults’ Ocular Manifestationsmentioning
confidence: 99%
“…Miller-Fisher syndrome or infarct-related central blindness are two neuro-ophthalmological consequences that might develop in extremely uncommon situations. 41 …”
Section: Adults’ Ocular Manifestationsmentioning
confidence: 99%
“…Previous research has demonstrated a link between COVID-19 infection and ocular complications, direct or indirect [5][6][7][8][9][10][11][12][13]. It has been well-documented that conjunctivitis, scleritis, orbital inflammatory disease, phlyctenular keratoconjunctivitis and retinal involvement may take place in COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization accepted the coronavirus disease 2019 (COVID- 19), raised from China in December 2019, as a global pandemic in March 2020 due to its quick spread and possible serious sequels and fatal results [1]. The pathogen is an enveloped RNA virus of the beta coronavirus family and is called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, microhemorrhages, cotton wool spots, and hyperreflective lesions have been documented as retinal findings in adult COVID-19 patients [17]. The existence of viral RNA has also been demonstrated in the conjunctiva and tear secretions of pediatric patients [19]. It has been postulated that pediatric COVID-19 patients have a better prognosis, shorter disease duration, and lower disease prevalence than adult patients [20,21].…”
Section: Introductionmentioning
confidence: 99%